Conversion from clinically isolated syndrome to multiple sclerosis: what paraclinical tests findings are the most characteristic? - Malciūtė, M.; Čelpačenko, I.; Stankevičiūtė, R.; Balnytė, R. (Neurologijos seminarai, 2021)
Background. Multiple sclerosis (MS) is a chronic demyelinating disease with clinical onset usually manifesting as clinically isolated syndrome (CIS). Approximately 70% of people with CIS convert to MS. Therefore, there is a pressing need to identify the most characteristic paraclinical test findings to predict CIS conversion to MS. Aim. The aim of this study was to establish the most characteristic paraclinical test findings for the identification of CIS conversion to MS. Materials and methods. A retrospective data analysis was performed in patients diagnosed with demyelinating encephalomyelitis according to ICD-10 (International Classification of Diseases Tenth Revision), codes G37.8 (other specified demyelinating diseases of central nervous system) and G37.9 (demyelinating disease of central nervous system, unspecified). In clinical practice, these diagnoses are called CIS. The data were obtained from medical records and included findings of paraclinical tests (magnetic resonance imaging (MRI), IgG levels and oligoclonal bands (OCBs) in cerebrospinal fluid (CSF), and brainstem auditory evoked potential (BAEP)) and final diagnosis. The patients were divided into 2 groups according to the final diagnosis (MS group and non-MS group) and into 3 age groups (18-30, 30-50, >50 years old). The prevalence and statistical difference of paraclinical tests were estimated between the groups. Chi-squared test was used to compare between categorical variables. Mann-Whitney U test was used to compare between the groups. The association between two quantitative variables was determined using Spearman correlation co-efficient. Results were interpreted as statistically significant when p-value <0.05. Results. A total of 138 cases were included in the study. 49 patients converted to MS (35.5%), other 89 patients (64.5%) were diagnosed with other diseases than MS. Unspecified MRI lesions (χ2=4.328, p=0.037, n=40), elevated IgG levels (χ2=10.793, p=0.001, n=36), and positive OCBs in CSF (χ2=34.859, p<0.001, n=30) were more prevalent in MS group compared to non-MS group. Moreover, lesions detected by the BAEP test were also more frequent among MS group (χ2=10.924, p<0.001, n=17). Conclusions. The results indicate that pathological CSF findings (positive OCBs, elevated IgG levels) and prolonged BAEP latency are characteristic in patients with CIS who later progress to MS. Unspecified brain MRI lesions are also distinctive for MS patients; however, this result should be interpreted with consideration due to methodological reasons